Henry Clay : the essential American - Heidler, David Stephen, 1955- (Random House, 2010)
Speaker of the House, senator, secretary of state, five-time presidential candidate, and idol to the young Abraham Lincoln, Henry Clay is captured in full in this rich and sweeping biography that vividly portrays all the drama of his times.